A STUDY OF STUDENT LEARNING DISCIPLINE IN SENIOR HIGH SCHOOL - Rini, Endah Febri Setiya; Aldila, Febri Tia; Wirayudha, Ricky Purnama (LPPM Universitas Jambi, 2023)
Discipline is the attitude of a person who is in accordance with the rules or regulations that apply both arising from his self-awareness and because of sanctions or punishments that have been applied so as to create order and regularity. This study uses a descriptive method with a quantitative approach which aims to analyze information about the description of the disciplined attitudes of class X MIPA students at SMA Negeri 8 Muaro Jambi for the 2020 academic year. The data was tested using the SPSS application. Based on descriptive statistical analysis, it was obtained that the students' discipline attitude was not good in class and outside class. Evidenced by the highest percentage of 51.7%